Shell-model Investigations in the p1/2g9/2 Space - Cerne,Axel (2025)
The goal of the present work is to investigate possible improvements to established shell-model interactions concerning atomic nuclei in the mass A=90, N=Z regime. These investigations consist of generating energy spectra for the isotopes Pd-94, Cd-94, Ag-95, and Cd-95 close to the proton drip line, as well as an investigation of the transition probabilities between selected states in Ag-95. Data was generated using the shell-model code ANTOINE, and was evaluated for the GF1 interaction as well as for two newly developed p1/2g9/2-model space interactions based on GF1 and the so-called JUN45 interaction, called Dp1g9 and Fp1g9, respectively. The present work was conducted in parallel with this development, based on the minimization of binding energy shift and mean level deviation for two sets of isotopes in the mass region of interest. Randomized sampling of two-body matrix elements, fundamental in the description of effective nucleon-nucleon interactions, was used to compare the sensitivity of the three shell-model parametrizations. The quality of comparison between predicted and experimental excitation energies was measured using a least square fit. It is shown that the Dp1g9 and subsequent Fp1g9 constitute a satisfying improvement of level descriptions in the four nuclei studied. In light of this improvement, the decay scheme of Ag-95 could successfully be revised, a conclusion supported by a transition-rate analysis. The present work leaves room for the original, now extended goal: to incorporate the lower lying p3/2 and f5/2 orbitals, which would imply a more complete description of medium-mass, neutron-deficient nuclei.
Keywords: Nuclear shell model; Isospin; Two-body matrix element; single-particle energy; Interaction; Mirror energy difference